Pengembangan Media Pembelajaran Chatbot Berbasis Smojo.AI Pada Pembelajaran IPA Kelas VI Di Sekolah Dasar - Ermayanti Tiodora Bakara; Mahmud Alpusari; Intan Kartika Sari (STKIP Subang, 2026)
The purpose of this study is to develop a chatbot learning media based on Smojo.ai that is feasible and practical for use in Natural Science (IPA) subjects for grade 6 of SDN 96 Pekanbaru, especially on the Solar System material. This research is motivated by the limited variety of learning media in schools which are still dominated by conventional media. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicate that the developed product is declared Very Feasible and Very Practical. The data analysis technique used is descriptive percentage statistics. The results of the study show that: (1) The results of validation by material, media, and language experts obtained an average score of 90.66% with a very feasible category; (2) The results of small group trials with students obtained a score of 91.09% with a very practical category; and (3) The results of practical trials by teachers obtained a score of 90.83% with a very practical category. Based on these findings, it can be concluded that the chatbot learning media based on Smojo.ai is very practical.